Celastrus paniculatus: A Bibliometric Assessment of Global Publications Output during 2001-18 - Ahmed, K.K. Mueen; Gupta, B.M.; Singh, N.K.; Thakur, V.K.; Kumar, Ashok (Pharmacognosy Reviews)
A bibliometric analysis of global research output on the Celastrus paniculatus plant is presented based on selected quantitative and qualitative indicators, using Scopus international database during 2001-18. The study analyzed publication and citations data on a series of bibliometric measures, like growth rate, citations impact, international collaborative papers, most productive countries, organizations, authors, journals and highly cited papers. The Celastrus paniculatus global publications registered an annual average growth rate of 16.55% and its citation impact averaged to 14.43 citations per paper. India alone accounting for the highest publication share (73.33%), whiles all other 9 countries from 1.67% to 7.14% during 2001-18. 99.77% global publication share and more than 100.0% citation share has been contributed by only top 10 countries during 2001-18. Brazil (8.25), Italy (2.51), USA (1.75) and Iran (1.42) registered comparatively the higher relative citation index among top 10 countries during 2001-18. Mohanlal Sukhadia University, Udaipur, India and Banaras Hindu University, Varanasi, India (4 papers each) were the two the most productive organizations and F. Borrelli and A.A. Izzo (4 papers each) were the two most productive authors. Journal of Ethnopharmacology (9 papers) and Phyomedicine (5 papers) were the two leading journals contributing research on this plant.
Keywords: Celastrus paniculatus; Medicinal plant; Global publications; Citations; International collaborative papers; Bibliometrics; Scientometrics